The mental health impact of physical inactivity: A study on UAE adolescents - Faten Mahmoud Diab; Shatha AL-Sharbatti; Abdalla Tamer Eltanbadawy; Rami Aws Alfahad; Ghada Elsayed Elgarawany (PLoS ONE, 2025)
Mental and physical health are essential for well-being, particularly during adolescence. The study aimed to assess the prevalence, factors, and relationship between physical inactivity and depression, and to determine the predictors of depression among adolescents in the UAE. A cross-sectional study was conducted among students in grades 9–12 from selected schools in the UAE. The study included adolescents of all genders and all nationalities. Two standardized questionnaires were employed: the “Physical Activity Questionnaire for Adolescents (PAQ-A)” to evaluate physical activity levels and the “Centre for Epidemiologic Studies Depression Scale (CES-D)” to assess symptoms of depression among the participants. Correlation test, independent t-test, chi-square test, bivariate and multivariate logistic regression analyses were used, with significance set at p < 0.05. The study included 365 participants, with the majority being over 14 years old (68.7%), female (60%), and in grade 10 (32.2%). The prevalence of depression and physical inactivity was 51.2% and 68.8%, respectively, and a significant negative correlation was found between depression and physical activity scores. Significant positive correlations are found between depression and grade level, and chronic health problems, and a negative correlation with crowding index. Significant negative correlations are found between physical activity, age, grade level, and chronic health problems. Predictors of depression are physical inactivity, female gender, overweight and obesity, and having a chronic disease. The study reveals a high prevalence of depression and physical inactivity among adolescents in the UAE. Consequently, physical activity may serve as a key protector against depression, and it potentially influences mental health through many physiological, neurological, and behavioural pathways. This underlines the critical need for interventions aimed at promoting physical activity.